Grover Method Analysis On Financial Distress In IDX Insurance Companies With Loss - Fitriani, Annisa; Khaerunnisa, Indar (inovator, 2025)
Insurance hold a crucial role in protecting against unexpected financial risks, but insurance faces profitability challenges that could potentially trigger financial distress. This study aims to analyze financial distress using the Grover method and to determine the influence of the Grover method's financial ratios are Working Capital to Total Assets (WCTTA), Earnings Before Interest and Tax to Total Assets (EBITTA), and Return on Assets (ROA) on financial distress. This study uses a descriptive quantitative method to analyze 9 insurance companies listed on IDX that experienced losses and drastic profit declines during 2018-2023. Secondary data were processed using Excel and SPSS 20 with the data analysis technique is Grover's method, descriptive statistical tests, classical assumption tests, multiple linear regression, and hypothesis test. The results show that average G-Score of ABDA, ASJT, LPGI, AHAP, ASBI, ASMI, BHAT, MREI, VINS falls within the safe zone, but BHAT is indicated potencial bankrupt on 2022-2023.The variables WCTTA and EBITTA have a significant positive effect on financial ditress, while ROA has a significant negative effect on financial distress. Further research is recommended to expand the sample, variables, and study period for more comprehensive results.